Lacanian Neuropsychoanalysis Lost in Psychologization - Jan De Vos (EJP import test, 2024)
Summary: In this article I scrutinize John Dall-Aglio’s project of a Lacanian neuropsychoanalysis informed by and inspired on Adrian Johnston’s philosophy of Transcendental Materialism. My aim is to mount a radical Freudo-Lacanian critique on both post-Freudian and neo-Lacanian projects of neuropsychoanalysis claiming that both strands end up psychologizing psychoanalysis and thus betray psychoanalysis’s arguably non-psychological subject of the unconsciousness. In this respect, I showcase that Dall-Aglio’s extensive reliance on Mark Solms and Jaak Panksepp and their highly psychologized research and writings is deeply problematic. When in neuropsychoanalytic parlance signifiers such as “behaviour,” “mental functions,” and “mental states,” pop up, it must be stated clearly, that we, psychoanalysts, do not do “the mental” and we not do “behaviour”; we do not do psychology. Moreover, I argue that neuroscience cannot be a “first science” as it itself needs to rely on psychological frameworks in order to correlate “the mental” to neurobiology. Or, starting out from the truths of psychoanalysis one can only encounter the brain as something filled with the lies of psychology. If then the question arises, whether Lacanian theory could offer “the true truths” to put under the MRI or relate to brain chemistry, one cannot but observe that to operationalize the subject of the unconscious one inescapably ends up turning psychoanalysis into yet another psychology. This is particularly clear in the clinical implications proposed by (Lacanian) neuropsychoanalysis, as these cannot but entail stepping into the rickety vessel of psychology and psychologization, betraying the very subject as being the subject of its own desubjectivitation.
Keywords: Neuropsychoanalysis; neuroscience; Lacan; Freud; Solms; Transcendental Materialism